2022
DOI: 10.1002/ese3.1275
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on thermal performance of battery module with LCP‐AFC cooling system applied in electric vehicle

Abstract: To improve the thermal performance of electric vehicle batteries, a novel cooling system of liquid cold plates coupled with air flow channels (LCP-AFC) for battery thermal management was proposed. Three-dimensional models were established for simulation. The effects of five factors on the heat dissipation of the electric vehicle battery module were studied, which included the battery discharge rate, inlet temperature of cooling liquid, nanofluids, airflow velocity, liquid, and air flow directions. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…Abdelkareem [118] compared different heat-dissipation capacity-enhancement methods for batteries, including air cooling, liquid cooling, heat pipes, and phase change material and found that the nanofluid effectively enhanced the heat-dissipation capacity. Guo [119] proposed a type of battery cooling system with a liquid cold plate and analyzed the different factors influencing the heat-dissipation performance. The simulation results showed that the maximum temperature and temperature differences were separately reduced.…”
Section: Nanofluid Application In Electric Vehiclesmentioning
confidence: 99%
“…Abdelkareem [118] compared different heat-dissipation capacity-enhancement methods for batteries, including air cooling, liquid cooling, heat pipes, and phase change material and found that the nanofluid effectively enhanced the heat-dissipation capacity. Guo [119] proposed a type of battery cooling system with a liquid cold plate and analyzed the different factors influencing the heat-dissipation performance. The simulation results showed that the maximum temperature and temperature differences were separately reduced.…”
Section: Nanofluid Application In Electric Vehiclesmentioning
confidence: 99%